2013
DOI: 10.3389/fpls.2013.00307
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis DREB2 genetic pathway is constitutively repressed by basal phosphoinositide-dependent phospholipase C coupled to diacylglycerol kinase

Abstract: Phosphoinositide-dependent phospholipases C (PI-PLCs) are activated in response to various stimuli. They utilize substrates provided by type III-Phosphatidylinositol-4 kinases (PI4KIII) to produce inositol triphosphate and diacylglycerol (DAG) that is phosphorylated into phosphatidic acid (PA) by DAG-kinases (DGKs). The roles of PI4KIIIs, PI-PLCs, and DGKs in basal signaling are poorly understood. We investigated the control of gene expression by basal PI-PLC pathway in Arabidopsis thaliana suspension cells. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 96 publications
0
44
0
Order By: Relevance
“…5 Transcriptomic studies of Arabidopsis cells in suspension using CATMA microarray chips, 6 allowed us to establish a list of genes that showed an altered expression for each inhibitor. [7][8][9] Comparing the lists showed an over representation of genes for which wortmannin and edelfosine (or wortmannin and U73122) had the same effect. 9 The common effect of inhibiting PI4K and inhibiting PI-PLC is to decrease the total amount of products generated by PI-PLC (Fig.…”
Section: Please Scroll Down For Articlementioning
confidence: 93%
“…5 Transcriptomic studies of Arabidopsis cells in suspension using CATMA microarray chips, 6 allowed us to establish a list of genes that showed an altered expression for each inhibitor. [7][8][9] Comparing the lists showed an over representation of genes for which wortmannin and edelfosine (or wortmannin and U73122) had the same effect. 9 The common effect of inhibiting PI4K and inhibiting PI-PLC is to decrease the total amount of products generated by PI-PLC (Fig.…”
Section: Please Scroll Down For Articlementioning
confidence: 93%
“…3,4 In the Arabidopsis thaliana genome, 4 type III-PI4K genes can be found, clustered into 2 a and 2 b subtypes. The AtPI4KIIIa2 is more likely a pseudogene.…”
Section: Introductionmentioning
confidence: 99%
“…DREB2D expression is not stimulated by the inhibitors of these enzymes, while DREB2F and DREB2G transcripts could never be detected in any of the conditions tested. 7 …”
mentioning
confidence: 99%
“…6 The PI-PLC/DGK pathway is active in nonstimulated Arabidopsis cells or plants. 7,8 We recently showed that this basal activity negatively regulated the expression of DREB2A, DREB2B, DREB2C, DREB2E, and DREB2H genes. Indeed, when inhibiting the activity of PI-PLC by edelfosine or U73122, or when inhibiting the activity of DGK by R59022 or R59949, the expression of these genes was upregulated in Arabidopsis suspension cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation